Cyclical Remedy Complexes: Their Origin within Traditional Chinese Medicine and Relevance for Miasmatic Theory - Kantor, Jerry M. (Homœopathic Links, 2017)
The roots of cyclical remedy analysis within traditional Chinese medicine's Five Phases theory are introduced. Relevance for clinical practice including illness interpretation, preventive application via a self-diagnosis mandala, and a more coherent understanding of the five original miasms (expressing five core existential dilemmas) are explained. This article presents a case illustration of anorexia nervosa and an analysis of three conditions: Alzheimer's disease, cancer of the breast, and cancer of the large intestine.
Keywords: Arsenicum album; Alzheimer's disease; Cancer; Cyclical remedy analysis; Five Phases theory; Homeosiniatry; Lapis albus (initial); Sense Dimensional Analysis